Breast Cancer Screening Access Among Low-Income Women Under Social Health Insurance: A Scoping Review - Hastuti, Sari (YCAB Publisher, 2024)
Background: Breast cancer is the most prevalent cancer among women worldwide. Due to its unknown causes, secondary prevention is highly encouraged for case early detection. Unfortunately, some women face difficulties in accessing it, even though they are covered by social health insurance. Objective: This study aimed to identify previous studies that mapped the various aspects within the domain of breast cancer screening access among low-income women under social health insurance. Design: This study used a scoping review method, following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) checklist. Data Sources: The electronic databases were searched in PubMed, Scopus, and EBSCO identified 115 articles. After the selection process involves two main stages, we found 7 studies included for the full review. Methods: Data charting is used for the data extraction. Thematic analysis is conducted to address the research question. Results: Social Health Insurance has a positive influence on access to breast cancer screening. Based on the Levesque framework, access is conceptualized in five dimensions, namely approachability, acceptability, availability, affordability, and appropriateness. Some aspects are found as variations of the original concept proposed as evidence from the field. Conclusion: The Levesque framework remains relevant to the experiences of low-income women. The variations observed emphasize the need for tailored approaches to healthcare delivery, providing opportunities for improving access.